Effects of Hip Joint Angle on Quadriceps Recruitment Pattern During Knee Extension in Healthy Individuals: Analysis by Ultrasound-Based Shear-Wave Elastography - Deng, Weixin; Lin, Ming; Yu, Suiqing; Liang, Hongying; Zhang, Zhijie; Tang, Chunzhi; Liu, Chunlong (Frontiers in Physiology, 2022)
Purposes: To detect the effects of hip joint position on the quadriceps recruitment pattern of different resistance levels of rectus femoris (RF), vastus intermedius (VI), vastus lateralis (VL), and vastus medialis obliquus (VMO) in healthy people during knee extension. Methods: Twenty healthy females performed isometric knee extension contractions at 0%, 10%, 20%, and 30% of maximal voluntary isometric contraction (MVIC) with a 90° and 0° hip angle. Ultrasound shear-wave elastography was used to evaluate the shear elastic modulus of RF, VI, VL, and VMO during resting and contraction states. Results: At resting state, stiffness of RF was about 50% higher at 0° compared with at 90° of the hip (p<0.01). There were significant differences in comparisons between 0% and 10% MVIC, 10% and 20% MVIC, and 20% and 30% MVIC in the four muscles, except that there was no significant difference between 20% and 30% MVIC for RF. There was a significant positive correlation between muscle stiffness and resistance level (r=0.78-0.94, p<0.001). Conclusions: Hip joint position had effects on the quadriceps recruitment pattern of different resistance levels in healthy people during knee extension.